The Influence Of The School Environment On Students' Learning Motivation In Private Madrasah Aliyah Hidayah Of The Khalipah Bookie - Hariani, Endang Sri; Nasution, Herry Syahbannuddin (At-Tarbiyah: Journal of Islamic Religious Research and Education, 2023)
This research approach is a quantitative approach, namely research where the data obtained is related to numbers which causes the use of statistical analysis techniques. The results of the research in this thesis, the school environment at Madrasah Aliyah Hidayah Private Bandar Khalipah is in the "enough" category. This can be seen from the average school environment at Madrasah Aliyah Hidayah Private Bandar Khalipah, which is 62.36 which is in the interval 56.80 - 68.01. The learning motivation of students at Madrasah Aliyah Private Hidayah Bandar Khalipah is in the "enough" category. This can be seen from the average student learning motivation at Madrasah Aliyah Hidayah Private Bandar Khalipah, which is 54.57 which is at intervals of 48.62 - 60.49. Based on the results of the t test, it can be seen that the first alternative hypothesis (Ha) test is accepted. Hypothesis testing is done by comparing the results of tcount with ttable. From the table of t test results, the tcount value is -2.349. Meanwhile, for ttable with a significance level of 0.05, a ttable value of 1.6759 was obtained. The comparison between the two results: tcount > ttable (¬2.349 > 1.6759). The significance value of t for the school environment variable is 0.03 and this value is smaller than the probability of 0.05 (0.03 <0.05). So that in this test it shows that Ha is accepted and Ho is rejected. This means that there is an influence between the school environment on student learning motivation at Madrasah Aliyah Private Hidayah Bandar Khalipah.